Radiation use efficiency is largely unaffected by plant density in maize (Zea mays L.): A review - Gonzalez Abba, Hugo; Bonelli, Lucas; Alfonso, Carla; Echarte, María Mercedes; Lewczuk, Nuria; Sinclair, Thomas R.; Echarte, Laura (Wiley, 2026)
Crop shoot mass production is often estimated from intercepted photosynthetically active radiation (iPAR), which when divided into accumulated shoot mass gives radiation use efficiency (RUE) for mass production. Management practices signif icantly influence mass production and are frequently evaluated through their effects on iPAR and RUE. While plant density’s effect on iPAR is well recognized, mainly through its influence on leaf area index (LAI), its impact on RUE has received com paratively limited attention. Theoretical derivations suggest that RUE should remain relatively stable across differing LAI, with potentially slightly smaller values at very low LAI. This study provides a comprehensive review of existing literature on the effects of plant density on RUE under optimal growing conditions in maize (Zea maysL.),examiningfactorscontributing to variability in RUEresponsestoplantden sity reported across studies. Results indicate a general agreement that RUE is largely unaffected by plant density within the tested range of LAI and for crops grown under non-stressed conditions.